Thermal analysis of magnetohydrodynamics (MHD) Casson fluid with suspended iron (II, III) oxide-aluminum oxide-titanium dioxide ternary-hybrid nanostructures - Kaneez, Hajra; Baqar, Awab; Andleeb, Irum; Bilal Hafeez, Muhammad; Krawczuk, Marek; Jamshed, Wasim; Eid, Mohamed R.; Abd-Elmonem, Assmaa (Journal of magnetism and magnetic materials, 2023)
•Steady boundary layer flow of Casson ternary hybrid nanofluid is constructed.•A non-Fourier heat transfer model is utilized for energy transport.•Single phase ternary hybrid model is considered.•Galerkin Finite element method (G-FEM) is adopted to find the approximate solutions.•Temperature distribution has revealed a tendency toward reducing thermal relaxation time. This study is carried out to enhance and analyze the thermal performance of non-Newtonian Casson fluid by immersing Ternary hybrid nanoparticles Fe3O4-Al2O3-TiO2 uniformly. To model the behaviour of such complex phenomena mathematically, a system of complex transport differential equations is developed by utilizing a non-Fourier heat transfer model for energy transport. The non-dimensional system of transport equations involving physical parameters is analyzed numerically by employing the Galerkin finite element methodology (G-FEM). The simulations predicted promising enhanced heat transfer characteristics in Ternary hybrid Casson fluid. The Casson fluid parameter has shown remarkable behavior on temperature distribution. Ternary hybrid nanoparticles have increased the overall thermal conductivity of the fluid and consequently, the temperature distribution is significantly raised. Hence ternary hybridity of nano-structures in Casson fluid is shown as an effective technique in improving the thermal performance of complex fluid.